ONE HEALTH APPROACH TO EMERGING ZOONOTIC DISEASES IN NIGERIA - UGWU, Eunice Ngozi (Multi-Disciplinary Research and Development Journals Int'l, 2025)
Emerging and re-emerging zoonotic diseases pose a significant and growing public health threat in Nigeria, driven by intensified human–animal–environment interactions, urbanization, deforestation, climate variability, and weak surveillance systems. This study examines the application of the One Health approach to the prevention, detection, and control of emerging zoonotic diseases in Nigeria, with particular focus on multisectoral collaboration, integrated surveillance, and community engagement. Using a mixed-methods explanatory sequential design, quantitative data were collected from 492 stakeholders across human, animal, and environmental health sectors, complemented by qualitative interviews, focus group discussions, and consultative workshops. Findings reveal moderate awareness and generally positive attitudes toward One Health collaboration; however, implementation remains inconsistent. Significant gaps were identified in integrated surveillance, routine data sharing, joint outbreak response, and balanced capacity across sectors—particularly within environmental health services. Structural barriers such as fragmented institutional mandates, inadequate funding, and unclear coordination mechanisms continue to limit operationalization of One Health principles. Despite these challenges, evidence from past outbreaks, including Lassa fever, demonstrates that coordinated multisectoral responses improve outbreak containment and response efficiency. The study concludes that while Nigeria has adopted One Health policies, translating these into sustained, operational practice requires institutionalized collaboration, interoperable surveillance systems, equitable capacity building, and strengthened community engagement to reduce the burden of zoonotic diseases and enhance national health security.